Dietary administration effects of fenugreek seeds on skin mucosal antioxidant and immunity status of gilthead seabream (Sparus aurata L.). Issue 75 (April 2018) - Guardiola, F.A.; Bahi, A.; Jiménez-Monreal, A.M.; Martínez-Tomé, M.; Murcia, M.A.; Esteban, M.A.
Abstract: Improving fish defense through the preventive administration of immunostimulants has an important role in controlling the outbreak of the disease in aquaculture. As a continuity of our previous studies, this paper describes the effects of dietary fenugreek ( Trigonella foenum graecum ) seeds on the skin mucosal antioxidant status and immune response of gilthead seabream ( Sparus aurata L.). Fish were fed with four experimental diets: one a basal diet (control) and three diets with powdered fenugreek seeds incorporated in the fish feed at 1%, 5%, and 10%. After eight weeks of feeding, free radicals scavenging and antioxidant assays were assessed in skin mucus by measuring the peroxidation of phospholipid liposomes, hydroxyl radical and hydrogen peroxide scavenging, measurement of total antioxidant activity and the determination of antioxidant activity in a linoleic acid system. The skin mucosal immune response was evaluated by measuring the IgM levels and some enzymatic activities (peroxidase, antiprotease, protease, esterase, and ceruloplasmin). Our results demonstrated that fenugreek inclusion improved the hydroxyl radical scavenging capacity and conferred very high antioxidant activity. Besides, only the highest supplementation level (10%) was able to augment the peroxidase and protease activities confronted by a general decrement in the antiprotease activity in the experimental fed groups with 1% and 10%. These results suggest that the dietary administration of fenugreek at the higher inclusion dose enhances the skin mucosal immunity response and the antioxidant status of gilthead seabream a species with one of the highest rates of production in marine aquaculture. Highlights: Effects of fenugreek diets on the antioxidant and immune status in skin mucus of gilthead seabream have been studied. For the first time, the skin mucus antioxidant capacity has been evaluated after herbal dietary administration. Fenugreek inclusion boosts the free radicals scavenging and antioxidant activity in skin mucus. The highest dose of fenugreek (10%) was able to enhance the mucosal immune responses. Some enzymatic activities are increased in skin mucus by fenugreek supplementation.